State Sovereign Immunity in Suits to Enforce Federal Rights - Samuel H. Liberman (Washington University Law Quarterly, 1977)
This Article attempts to clarify the doctrine of sovereign immunity and its exceptions in its application to federal question cases. First, section II identifies the concept of state sovereign immunity. Section III discusses the liability of state officials, the doctrine principally used to avoid state immunity. Although the cases in section III involve non-federal claims, they are important because of their pervasiveness in the non-federal area and because they have often been applied without close analysis in federal question cases. Section IV, the heart of this Article, discusses the application of the doctrine of state sovereign immunity in federal question cases.
Keywords: Federal jurisdiction; Government immunity and liability